ГЕМОЛИТИЧЕСКАЯ СТОЙКОСТЬ ЭРИТРОЦИТОВ ПРИ ОСТРОМ КОРОНАРОГЕННОМ СТРЕССЕ И ЕЁ ФУНКЦИОНАЛЬНЫЕ ВЗАИМОСВЯЗИ - А. А. Михайлис (Архивъ внутренней медицины)
In the work the special features of the erythrocytes acid resistance (EAR) are studied dynamics at the instable stenocardia and the myocardial infarction (Q-positive and Q-negative). It is revealed that it bears phase character and depends on gravity of the coronary stress. Correlations EAR with other clinical laboratory indices are described. It is established that the development of stress is characterized by strengthening the degree of the coupling of interaction between the erythron and other systems of organism. The predominance of the stress-realizing system activity leads to the increase EAR. Reduction in the stress-realizing activity and predominance of the stress-limiting system leads to the reverse dynamics of acid-hemolytic erythrograms.